The hnRNPK/A1/R/U Complex Regulates Gene Transcription and Translation and is a Favorable Prognostic Biomarker for Human Colorectal Adenocarcinoma - Li, Yixin; Wang, Hui; Wan, Jiajia; Ma, Qian; Qi, Yu; Gu, Zhuoyu (Frontiers in Oncology, 2022)
Heterogeneous nuclear ribonucleoproteins (hnRNPs) are emerging as a crucially important protein family in tumors. However, it is unclear which family members are essential for cancer progression, and their diverse expression patterns and prognostic values are rarely reported. In this work, we found that the expression levels of hnRNPs were all upregulated in colon adenocarcinoma (COAD) and rectal adenocarcinoma (READ) tissues. Immunohistochemical staining revealed that hnRNPA1, hnRNPA2B1, hnRNPC, hnRNPK, hnRNPR, and hnRNPU are overexpressed in colorectal adenocarcinoma. Additionally, the promoter methylation levels of hnRNPs were significantly elevated or decreased, and multiple genetic alterations of hnRNPs were found in colorectal adenocarcinoma patients. Correlation analysis showed that the expression levels of hnRNPs were positively correlated with each other. Furthermore, we demonstrated that high expressions of hnRNPA1, hnRNPK, hnRNPR, and hnRNPU were associated with better overall survival rates for colorectal adenocarcinoma patients. The co-expression network and functional prediction analysis indicated that hnRNPK/A1/R/U was involved in cellular gene transcription and translation. Moreover, hnRNPK/A1/R/U complex was identified and confirmed by mass spectrometry and co-immunoprecipitation. RNA sequencing analysis revealed that the transcription factor hnRNPK regulated transcription and translation of related genes. Finally, through establishment of stable cell lines in vitro, we verified that hnRNPK was a favorable factor in human colorectal adenocarcinoma which promoted immune cell infiltration and inhibited tumor growth. Our findings illustrate that the hnRNPK/A1/R/U complex is a favorable prognostic biomarker for human colorectal adenocarcinoma. Targeting hnRNPK during transcription and translation could be a promising therapeutic strategy for colorectal adenocarcinoma treatment.